On a coastal breeze [large type] - Fisher, Suzanne Woods (Fisher, Suzanne Woods. Three Sisters Island, 2020)
"For Madison Grayson, life is good. Newly licensed as a marriage and family therapist, she can't wait to start her practice. Despite the unfortunate shortage of eligible bachelors on the island--they're all too young, too old, or too weird--Maddie feels like she's finally found her sweet spot. Not even one panic attack in the last year. Not one. And then Ricky O'Shea drops in. Literally. Floating down from the pure blue sky, the one man in the world she hoped never to see again--the one who'd been her archnemesis from kindergarten through her senior dance--parachutes into town, landing on Boon Dock, canopy draping behind him like a superhero. Ricky O'Shea. Now Pastor Rick, the new minister on Three Sisters Island. Time to panic."--Back cover.